The Role of Setting in the Golden Age Detective Novel - Stýblová, Žaneta (My University, 2018)
Analyses of crime fiction often focus on the plot, characters and their social positioning but tend to pay much less attention to the actual setting. Employing the concept of active and passive relationships of setting and plot, G. J. Demko’s notion of cultural and physical space as well as other theories of literary representation of place, the article discusses the role of setting in the Golden Age crime fiction, namely in Agatha Christie’s The Mysterious Affair at Styles and Third Girl.
Role místa v klasické britské detektivce
Keywords: Setting; space; crime fiction; detective novel; Golden Age; The Mysterious Affair at Styles; Third Girl; místo děje; prostor; detektivka; zlatý věk britské detektivky; Agatha Christie; Vražda na zámku Styles; Margery Allinghamová; Vražda v Black Dudley